Tactile dimensions of fabrics expressed by Japanese onomatopoeic words and phonemic features related to fabric luxuriousness and pleasantness - Hanada, Mitsuhiko (Frontiers in Language Sciences, 2023)
This study examined the perceptual dimensions in the tactile perception of fabrics (cloths). The participants were asked to touch, stretch, and curl 23 fabrics and report suitable onomatopoeic (mimetic) words to describe the hand feel for each fabric. The participants’ responses were collated into a contingency table of fabrics according to onomatopoeic words. The participants also rated the hand feel of the fabrics using bipolar semantic differential (SD) scales (heavy-light, thick-thin, soft-hard, elastic-inelastic, warm-cold, rough-smooth, luxurious-cheap, and pleasant-unpleasant). Three dimensions of thickness/heaviness, roughness, and softness were derived by factor analysis of the SD ratings with varimax rotation. Next, the dimensions of warmness/fullness/softness, roughness-smoothness, and elasticity/softness were obtained through correspondence analysis combined with sparse coding applied to the contingency table of fabrics by onomatopoeic words. However, these dimensions were not consistent with the factor dimensions obtained using factor analysis, which suggests that Japanese onomatopoeic words express the complex hand feel of fabrics. Finally, the luxuriousness and pleasantness of fabrics were also examined, and sensory characteristics and phenomes of onomatopoeic words related to these attributes were reported.